Fostering young people's support for participatory human rights through their developmental niches - Torney-Purta, Judith; Barber, Carolyn (American journal of orthopsychiatry, 2011)
The last 6 decades of empirical research on civic engagement among young people living in democracies and of the recognition of international human rights have seen the achievement of many milestones. This article focuses on some connections between these 2 areas and examines the ways in which everyday settings such as neighborhoods and the schools that exist within them can foster support for human rights (especially the practice of participatory rights) among adolescents. Secondary analysis of the International Association for the Evaluation of Educational Achievement Civic Education (CIVED) Study (data collected in 1999 from nationally representative samples of 14-year-olds in 28 countries) is presented. A cluster analysis of 12 attitudinal scales in 5 countries sharing the Western European tradition (Australia, England, Finland, Sweden, and the United States) is presented. A new conceptual model is also introduced, a modification of Super and Harkness's Developmental Niche. This model frames an analysis unpacking some findings from the CIVED Study and focusing on the everyday experiences and neighborhood niches for the development of participatory human rights. The larger message is that research on social justice attitudes among young people is a valuable form of social advocacy and action.